2017
DOI: 10.7287/peerj.preprints.2761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comprehensive simulation study on classification of RNA-Seq data

Abstract: Background RNA sequencing (RNA-Seq) is a powerful technique for transcriptome profiling of the organisms that uses the capabilities of next-generation sequencing (NGS) technologies. Recent advances in NGS let to measure the expression levels of tens to thousands of transcripts simultaneously. Using such information, developing expression-based classification algorithms is an emerging powerful method for diagnosis, disease classification and monitoring at molecular level, as well as providing potential markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We tested this hypothesis by applying machine learning algorithms on two groups of heifers that were bred in 2015 (year one) and 2016 (year two). Parallel random forest emerged as the algorithm with over 90% efficiency of classification nearly all trials executed, which confirms the potential of accurate classification of samples using RNA-seq data under the case-control framework 60,61 . The results show that while not one single gene emerges as a potential biomarker, the accumulated information of transcript abundance from multiple genes can be powerful for the identification of fertility potential in cattle.…”
Section: Discussionmentioning
confidence: 53%
“…We tested this hypothesis by applying machine learning algorithms on two groups of heifers that were bred in 2015 (year one) and 2016 (year two). Parallel random forest emerged as the algorithm with over 90% efficiency of classification nearly all trials executed, which confirms the potential of accurate classification of samples using RNA-seq data under the case-control framework 60,61 . The results show that while not one single gene emerges as a potential biomarker, the accumulated information of transcript abundance from multiple genes can be powerful for the identification of fertility potential in cattle.…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, a number of studies reported that the miRNAs were stable both in the body and in paraffin blocks, which provided better biomarkers of tumor classification (Baker, 2010;Iqbal et al, 2015;Lu et al, 2005;Matamala et al, 2015;Raponi et al, 2009;Zen and Zhang, 2012). Thus, some researchers proposed several methods to find miRNA biomarkers of the cancers, such as miRNA instance-based approaches and miRNA feature-based approaches (Breiman, 2001;Breiman et al, 1984;Zararsiz et al, 2017). Similar to the performance of using gene biomarker classification (Perez-Diez et al, 2007;van 't Veer et al, 2002;Wang et al, 2005), the reproducibility of the miRNA biomarkers has been challenged (Dupuy and Simon, 2007;Ein-Dor et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…PLDA may be a good choice for count based classifier after power transformation of data in all dispersion settings [47]. Recently, a few studies were performed to classify the sequencing data involving PLDA which concluded that PLDA classifier is somewhat similar to diagonal LDA and performs satisfactory over sequencing data [22,48].…”
Section: Poisson Linear Discriminant Analysis (Plda)mentioning
confidence: 99%